Powder metallurgical production of 316L stainless steel/niobium composites for Proton Exchange membrane electrolysis cells. (27th May 2019) - Daudt, N. F.; Hackemüller, F. J.; Bram, M.
ABSTRACT: In this study, a composite made of a porous stainless steel (SS) 316L substrate coated with Nb was investigated as a novel porous transport layer (PTL) for proton exchange membrane electrolysis cells (PEMECs). The fabrication of such SS316L/Nb composites using scalable and automatable powder metallurgical techniques as tape casting, screen-printing and field assisted sintering technology/spark plasma sintering (FAST/SPS) was described. Sintering behaviour and the interdiffusion at the SS316L/Nb interface were investigated. Powder metallurgical techniques such as screen-printing are the preferred method to achieve a porous Nb coating, while FAST/SPS is the preferred method for a better control of the SS316L/Nb interface by lowered interdiffusion. First electrochemical performance tests with SS316L/Nb composites demonstrate they have potential to replace the state-of-the-art titanium-based PTLs. The use of SS316L is expected to decrease manufacturing costs of PTLs, while the addition of niobium layer, due to its excellent corrosion resistance in acid environment, aims to improve PEMECs lifetime and performance.